Tributyltin bioaccumulation and toxic effects in freshwater gastropods Pomacea canaliculata after a chronic exposure: field and laboratory studies - Martínez, María L. (2017)
Freshwater samples and gastropod mollusks (Pomacea canaliculata) were collected at 5 sampling stations located along the lower Río de la Plata basin, Argentina, to assess the extent of tributyltin (TBT) contamination. Determined data revealed the presence of TBT and some of its breakdown products (dibutyltin: DBT, and monobutyltin: MBT) in all freshwater samples and also in soft tissues of P. canaliculata gastropods. Chronic bioassays (6 months) were performed using female gastropods that had been reared under laboratory conditions and exposed to a similar TBT concentration than the value determined in freshwater samples (1 µg L−1). The aims of this study were to evaluate the extent of TBT accumulation, the tissue distribution, and the effects on selected biomarkers (activity of superoxide dismutasa: SOD, activity of catalase: CAT, levels of total glutathione: t-GSH, lipid peroxidation, and activity of acetylcholinesterase: AChE). Gonads presented the highest accumulation, followed by the cephalopedal region, albumin gland, and finally hepatopancreas. Both metabolites, DBT and MBT, were also found. All exposed female animals presented development of a penis reflecting the potential of TBT as an endocrine disrupting chemical for this gastropod species. Results on the selected biomarkers confirmed additional adverse effects induced by TBT. An increase in CAT activity and changes in t-GSH levels are indicative of alterations on the cellular redox status. The inhibition of AChE could reflect signs of neurotoxicity. Altogether, these results reveal a negative impact on the health of this gastropod population.